Bridging Conducting Pedagogy and Digital Technology: Teachers’ Perceptions and Adoption Intentions toward a Webcam-Based Hand-Tracking Trainer - Firmansyah, Agus; Jaohari, Enry Johan; Ramadhan, Muhammad Yuda; Febiyanti, Widya (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to analyze teachers’ perceptions of the usefulness, ease of use, perceived learning, and adoption potential of the CONDUCT HandTrack Conducting Trainer a web application combining webcam hand-tracking, two-dimensional visualization, and real-time gesture scoring (perfect/good/miss) using the Technology Acceptance Model as an analytic lens. A descriptive quantitative approach complemented by qualitative data (embedded mixed-methods design) was applied to 21 teachers from teacher working groups (MGMP) in Subang Regency via a 56-item questionnaire (Likert 1–5). Descriptive analysis, Cronbach’s alpha reliability testing, Pearson correlation analysis, and thematic analysis showed perceived learning highest (mean 4.35; 96.2% agreement), followed by adoption potential (4.34) and training quality (4.22), while usability (ease of use) was lowest yet positive (3.83; α=0.83). Pearson correlations among constructs were strong (r=0.71–0.84; p<0.01), supporting the ease → usefulness → intention path indicatively at pilot scale. Application and training ratings were 4.76 and 4.48; all participants intended to pursue further training. The dominant barrier hand-detection accuracy explains the lower ease-of-use score, yet high perceived usefulness sustains adoption intention, a pattern consistent with utility-driven adoption. Theoretically, the study extends TAM and real-time-feedback evidence to in-service teachers on an embodied skill; practically, it guides the development of music-pedagogy technology toward tracking reliability, staged practice modes, and stakeholder-specific support.